Public finance in Sabah: voting for development? / Wee Chong Hui - Wee, Chong Hui (2008)
Both the Federal Government and the State Government jointly and independently manage public finance under their respective jurisdictions in Sabah. Sabah has been described as having a favoured financial position in the Malaysian Constitution. There have also been reports of arguments for increased federal financial allocations to the state, with recent calls after the 12th General Election saw a significant representation of Sabah in the ruling coalition. This paper analyses the contributions of both the Federal Government and the State Government to the economy in terms of growth and equity over the years. Fiscal federalism with respect to the state is examined against the changing circumstances of its open economy from 1963 until early 2008 (12th General Election).